Numerical simulation and experimental validation for design improvement of packer rubber. (2017) - Wang, Hanxiang; Chen, Shengshan; Liu, Yanxin; Zhang, Lijun; Zhang, Zhenning
As the packer plays an important role in the exploration of low permeability reservoirs, the sealing property of the dual-channel packer is studied in this paper. The finite element analysis software ABAQUS is used to optimise the sealing unit structure of the dual-channel packer. The influences of inner groove shape and structure of shoulder protection on the sealing property are investigated. Based on simulation results, the best inner groove shape and the structure of shoulder protection are confirmed. Furthermore, the validity of the simulation results is confirmed by performing experiments, which show that the dual-channel packer with optimised sealing unit can work reliably in 70 MPa and 170°C.